Mapping the infection pathways in human placentas - Omotoyosi Osalaye (BioScientist: The Salford Biomedicine Society Magazine, 2024)
This review explores the intricate mechanisms by which pathogens breach the placental barrier, a critical interface between mother and foetus. Despite its robust defensive structures, including the syncytiotrophoblast and underlying tissues, various microorganisms have evolved strategies to penetrate this barrier, leading to severe maternal and foetal health complications. The article examines three main categories of pathogens — bacterial, viral, and parasitic— and their distinct infection pathways. Notable examples include Listeria monocytogenes' use of surface proteins for cellular invasion, cytomegalovirus' manipulation of trophoblasts, and Toxoplasma gondii's evasion of immune responses. The impact of these infections on maternal and foetal health is substantial, potentially resulting in preeclampsia, preterm labour, congenital anomalies, and long-term developmental issues. Current research utilises advanced technologies such as high-resolution imaging, single-cell sequencing, and organoid models to elucidate molecular mechanisms and develop targeted therapies. The review concludes by highlighting the importance of understanding pathogen-placenta interactions for developing effective preventive measures, early detection techniques, and safe treatment options during pregnancy. Future directions emphasise the need for translational research to bridge laboratory findings with clinical practice, potentially reducing the burden of placental infections and their associated complications.